2009
DOI: 10.1016/j.hrthm.2008.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Real-time dominant frequency mapping and ablation of dominant frequency sites in atrial fibrillation with left-to-right frequency gradients predicts long-term maintenance of sinus rhythm

Abstract: Background-Spectral analysis identifies localized sites of high-frequency activity during atrial fibrillation (AF). We determined the effectiveness of using real-time dominant frequency (DF) mapping for radiofrequency ablation of maximal DF (DFmax) sites and elimination of left-to-right frequency gradients in the long-term maintenance of sinus rhythm (SR) in AF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
354
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 307 publications
(371 citation statements)
references
References 17 publications
13
354
3
1
Order By: Relevance
“…Subsequent studies supported the notion that the high DF (DF max ) sites play a role in the maintenance of AF in a significant number of patients. 592,593 …”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies supported the notion that the high DF (DF max ) sites play a role in the maintenance of AF in a significant number of patients. 592,593 …”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…At a mean of 9.3 ±5.4 months, freedom from AF after one or more ablation procedures was achieved in 88% and 56% of paroxysmal and persistent AF patients, respectively. 593 A more recent prospective randomized clinical trial of 232 patients with paroxysmal comes with a DF-based approach compared with PVI alone. 594 None of the writing group members incorporate DF mapping as a routine AF ablation strategy in initial or repeat ablation of PAF.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…As persAF is a more complex arrhythmia than pAF, the identification of atrial areas for successful ablation in patients with persAF remains a challenge due to the co-existence of multiple arrhythmogenic mechanisms [4,35]. Previous works have shown that the DF measured from AEGs correlates with the local main activation wave during persAF [9, 14,36].…”
Section: Mechanisms For Persaf Maintenancementioning
confidence: 99%
“…Recent studies have shown beneficial outcomes in persAF ablation by targeting rotors defined by points of singularity in phase maps [12,13]. Both HDF and phase mapping might help to identify potential AF drivers and ablation of those areas might contribute to AF treatment [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…According to studies in isolated sheep heart, most of the high frequency sources exist in the LA and at a critical frequency, a gradient develops between LA and RA. In a recent study, Atienza et al 48 demonstrated that elimination of LA to RA frequency gradients during ablation predicts long-term maintenance of sinus rhythm in AF patients. All these data clearly indicate that high-DF sites play a role in the maintenance of AF in a significant number of patients.…”
Section: Dominant Frequencies and Afmentioning
confidence: 99%